Space vector control of dual matrix converters based five-phase open-end winding drive - Salam, Zainal (Institute of Electrical and Electronics Engineers Inc., 2014)
This paper presents a novel five-phase open-end winding drive system supplied by the dual non-square matrix converter. The input to each of the matrix converter is three phase utility grid system and the output is five phase voltages with variable voltage and frequency. The two matrix converters feeding the five-phase open-end load are supplied from a common single three-phase utility source of 50 Hz. Space vector based PWM algorithm is developed to control the five-phase open-end load The proposed control technique eliminates the common-mode voltage across the machine winding and hence no zero sequence currents will be produced and therefore no isolated supply is required for the dual three-to-five phase matrix converter system. Further the proposed technique will enhance the five phase machine phase voltage to 1.5 times the input supply voltage. A simple R-L load is considered in the paper. The paper presents the analytical approach to obtain the expression of modulating signals that are used to generate the switching pulses for the matrix converter. Simulation results are presented to support the idea of the proposed modulation scheme.